Museums, Challenging Heritage and Social Media During COVID-19 - Kist, Cassandra (Museum and Society, 2020)
In this opinion piece I reflect upon museum social media trends during COVID-19 and consider what it could mean in terms of future online engagement and the (mis)alignment of practices with institutional social missions. In opposition to the recent focus on uplifting museum content and activities online, I investigate an overlooked question regarding the role of challenging heritage on social media during the pandemic. I end with a call for the sector to consider the complexities of including or excluding challenging heritage from current museum online activities and in turn, the opening or foreclosure of critical reflections at a pivotal time in history.